Vitamin d sufficiency in hemodialysis patients and its association with nutritional and clinical parameters - Barbara Perez Vogt; Francieli Delatim Vannini; Aline Araújo Antunes; João Henrique Castro; Pasqual Barretti Jacqueline (The Korean Society of Nephrology, 2012)
Renal failure is a complicating factor in the maintenance of vitamin D adequate levels, which can interfere in the patients' nutritional status. The aim of this study was to evaluate the association of serum 25-hydroxyvitamin D [25(OH)D] with clinical and nutritional parameters. Prevalent hemodialysis (HD) patients were submitted to a single evaluation about demographic characteristics, clinical data and laboratory measurements. Anthropometric measurements and electrical bioimpedance were performed to obtain BMI, percentage of standard MAMC (%MAMC), fat percentage (%Fat) and phase angle (PA). Deficiency was defined as a 25(OH)D level<15 ng/mL, insufficiency as 15-30 ng/mL and sufficiency as>30 ng/mL. Univariate models were constructed and the variables associated with 25(OH)D sufficiency were included subsequently in the multiple regression model. Statistical significance was p<0.05.One hundred twelve patients (59 male, 53 female) were included. Twenty seven (24.1%) were 25(OH)D deficient, 43 (38.4%) insufficient and 42 (37.5%) sufficient. In univariate regression, creatinin, albumin and PA were positively associated with serum 25(OH)D, while age, glucose, BMI and %MAMC were negatively associated. In multivariate regression, age and %MAMC were negatively associated with sufficiency. Most studied sample showed inadequate 25(OH)D levels. In our study, the result to be highlighted was the negative associations of 25(OH)D sufficiency with age and %MAMC, but all the findings suggest that fat interferes with vitamin D stores in HD patients.